2020
DOI: 10.1111/jcpt.13324
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors and trends of opioid prescribing for lower back pain in United States emergency departments

Abstract: What is known and objective: Current evidence-based guidelines for the treatment of acute low back pain (ALBP) recommend the use of opioid medications only after failure of nonpharmacological therapy, non-steroidal anti-inflammatory drugs and skeletal muscle relaxants and after thorough evaluation of risks and benefits. Despite this recommendation and the state of the opioid epidemic in the United States (US), opioids remain a common drug of choice for ALBP in the emergency department (ED). The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…There was no consensus on the additional benefit of combining other medications with NSAIDs. One study reported decreased opioid prescribing for patients who received either acetaminophen or NSAIDs [ 18 ], while other studies found no benefit from acetaminophen for the treatment of low back pain [ 12 , 22 ]. There was a similar disagreement on the effectiveness of muscle relaxants.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no consensus on the additional benefit of combining other medications with NSAIDs. One study reported decreased opioid prescribing for patients who received either acetaminophen or NSAIDs [ 18 ], while other studies found no benefit from acetaminophen for the treatment of low back pain [ 12 , 22 ]. There was a similar disagreement on the effectiveness of muscle relaxants.…”
Section: Reviewmentioning
confidence: 99%
“…There is widespread agreement on the limited use of opioids and their detrimental long-term effects. Despite recommendations against first-line use of opioids, however, there is a broad acknowledgment of overprescription and chronic use of opioids for patients in emergency departments [ 18 ] and following discharge [ 26 ]. We found no consensus on the reason for this discrepancy.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, multimodal analgesia has become more a standard to manage pain as effectively as possible, also reducing opioid exposure [91], without sacrificing patient comfort or impeding rehabilitation [92]. This is relevant if one considers that opioids remain a common drug of choice for acute LBP in the emergency department (ED) [93] and their use in ED has been associated with an increased length of stay [94].…”
Section: Multimodal Analgesia: the Way Forwardmentioning
confidence: 99%